Esporte e direitos humanos: uma análise da promoção da Igualdade nas relações desportivas - Moura, Alessandra Christine Bittencourt Ambrogi de (2023)
This paper aims to verify the effectiveness of the equality dimension of human rights in the context of sports relations. In order to understand how equality relates to sporting events, it is first necessary to understand the foundations of human rights equality, its scope and its coverage, and then to analyze the lex sportiva and sporting events. For this reason, an analysis is made of the philosophical, theological and legal aspects of equality, as well as its recognition as a human right, its formation for the dignity of individuals and its constitution as a fundamental right. Once this scope and scope have been delimited, an incursion is made into the phenomenon of sport to, at first, also delimit its scope with regard to the interpretation of this as a human and social right of a fundamental order; and then the formation of general sports rules, known as lex sportiva, is verified to observe against what this instance, in the name of the private autonomy of the sports chain, has been placing itself and how it has impacted the effectiveness of human rights. From this perspective, marked above all by the lack of effectiveness of human rights equality, which results in repeated discrimination and various conflicts of competence of the International Sports System, we seek to establish fair, equitable and isonomic ethical limits for the promotion of peace through sport. To achieve the proposed objectives, we opted for bibliographic and documentary research, collecting information from books, articles, magazines, newspapers, judicial decisions and other scientific materials, both human rights and Labor Law and Sports Law, and the analytical method was chosen in order to present and study the expressive cultural, social and economic impacts, which allowed the deepening of the theme